Pornography Addiction is Related to the Mental Status of Coastal Adolescents - Nugraha, M.Akbar; Handayani, Fitriya; Darni, Darni (Jurnal Ilmiah Ners Indonesia, 2025)
Pornography was one of the potential problems faced by adolescents because of sexual desire, curiosity, and effortless access. Pornography could cause psychological problems for adolescents. Adolescents in the city of Tarakan were exposed to much pornography and often watched pornographic shows. The level of pornography addiction in adolescents was not yet known, and the mental status of adolescents was unknown. This research aimed to determine and analyze the relationship between the level of pornography addiction and the mental status of adolescents in the coastal city of Tarakan. This research method was quantitative with a cross-sectional design. The data in this study was taken using a survey method with a sample size of 386 adolescents. Data were collected using the Pornography Addiction Screening Tool (PAST) and Strengths and Difficulties Questionnaire (SDQ) questionnaires. Results: Most of the female adolescent respondents were 51.8% with an average addiction level of 73.8%, and mental status results were normal at 73.3%, and there was a significant relationship between pornography addiction and the mental status of adolescents with a p-value 0,001. Conclusion: This research concluded that there was a significant relationship between pornography addiction and the mental status of adolescents on the coast of Tarakan City. The research recommended increasing digital literacy for parents in the coastal areas of Tarakan regarding the risks of the digital world, including pornography, integrating materials about the dangers of pornography addiction, mental health, and digital security into the curriculum or extracurricular activities, and developing positive community activities.